Film voices : interviews from Post Script - Duchovnay, Gerald, 1944- (SUNY series, cultural studies in cinema/video., 2004)
"This collection of interviews brings together major Hollywood directors and actors, independent filmmakers, screenwriters, and others to discuss the art, craft, and business of making movies. Whether it be Clint Eastwood or Francis Ford Coppola, Vittorio Storaro or Dede Allen, these filmmakers detail how they strive for quality, the price they pay to do so, and how new technologies and the business aspects of filmmaking impact all aspects of their creativity. Taken together, the interviews reveal much about filmmaking practices in and out of Hollywood."--Jacket